The 'critical trochanter angle' does not show superiority over the CCD angle in predicting varus stem alignment in cementless short-stem total hip arthroplasty. - Luger, Matthias; Feldler, Sandra; Pisecky, Lorenz; Allerstorfer, Jakob; Gotterbarm, Tobias; Klasan, Antonio (Archives of Orthopaedic and Trauma Surgery, 2023)
PURPOSE: Varus positioning of the femoral stem can affect the hip offset (HO). The critical trochanter angle (CTA) was introduced in 2019 as a novel geometric angle, to predict varus stem alignment in cementless straight stem THA. The aim of this study was to evaluate the applicability of the CTA as a predictor for stem alignment in THA with a cementless neck resecting short stem. PATIENTS AND METHODS: In this retrospective study, 106 patients (index surgery 2014-2019) with unilateral THA and a morphologically healthy contralateral hip as a reference (Kellgren-Lawrence ≤ 1) were included. A cementless short stem with meta-diaphyseal fixation and press-fit cup was implanted in all cases. Stem alignment, CCD angle, CTA and offset reconstruction were measured on preoperative and 3 months postoperative AP radiographs of the pelvis. RESULTS: Preoperative lower CTA and lower CCD angle were positively correlated (r = 0.472; p < 0.001). Higher varus stem alignment is correlated with lower CTA (r = - 0.384; p < 0.001) and lower CCD angle (r = - 0.474; p < 0.001). A CTA of 23.1° or lower showed a sensitivity of 59.1% and a specificity of 87.1% (AUC: 0.733) and a CCD angle of 132.75° or lower a sensitivity of 68.2% and a specificity of 80.6% (AUC: 0.77) for a varus stem alignment > 3°. CONCLUSION: The CTA is also applicable in cementless THA with a neck resecting short stem to evaluate risk of intraoperative varus stem positioning. The CCD angle shows higher sensitivity with marginally lower specificity. Therefore, the CTA is not superior in predicting varus stem alignment in short-stem THA. LEVEL OF EVIDENCE: IV.
EVALuna2:595231